COVID-19: Poor outcomes in patients with zinc deficiency. (November 2020) - Jothimani, Dinesh; Kailasam, Ezhilarasan; Danielraj, Silas; Nallathambi, Balaji; Ramachandran, Hemalatha; Sekar, Padmini; Manoharan, Shruthi; Ramani, Vidyalakshmi; Narasimhan, Gomathy; Kaliamoorthy, Ilankumaran; Rela, Mohamed
Highlights: Patients with coronavirus disease 2019 (COVID-19) had significantly low zinc levels in comparison to healthy controls. Zinc deficient patients developed more complications (70.4% vs 30.0%, p = 0.009). Zinc deficient COVID-19 patients had a prolonged hospital stay (7.9 vs 5.7 days, p = 0.048). In vitro studies have shown that reduced zinc levels favour the interaction of angiotensin-converting enzyme 2 (ACE2) with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein and likewise that increased zinc levels inhibit ACE2 expression resulting in reduced viral interaction. Abstract: Background: Zinc is a trace element with potent immunoregulatory and antiviral properties, and is utilized in the treatment of coronavirus disease 2019 (COVID-19). However, we do not know the clinical significance of serum Zinc levels in COVID-19 patients. The aim of this study was to determine the clinical significance of serum zinc in COVID-19 patients and to establish a correlation with disease severity. Methods: This was a prospective study of fasting zinc levels in COVID-19 patients at the time of hospitalization. An initial comparative analysis was conducted between COVID-19 patients and healthy controls. COVID-19 patients with zinc deficiency were compared to those with normal zinc levels. Results: COVID-19 patients ( n = 47) showed significantly lower zinc levels when compared to healthy controls ( n = 45): median 74.5 (interquartile range 53.4–94.6) μg/dl vs 105.8 (interquartile range 95.65–120.90) μg/dl ( p < 0.001). Amongst the COVID-19 patients, 27 (57.4%) were found to be zinc deficient. These patients were found to have higher rates of complications ( p = 0.009), acute respiratory distress syndrome (18.5% vs 0%, p = 0.06), corticosteroid therapy ( p = 0.02), prolonged hospital stay ( p = 0.05), and increased mortality (18.5% vs 0%, p = 0.06). The odds ratio (OR) of developing complications was 5.54 for zinc deficient COVID-19 patients. Conclusions: The study data clearly show that a significant number of COVID-19 patients were zinc deficient. These zinc deficient patients developed more complications, and the deficiency was associated with a prolonged hospital stay and increased mortality.